THE ANTHROPOLOGICAL ANGLE OF ANTOA – A NEW THEORY OF ART - Will, Ralf G (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Aim of this article is to shed light on anthropological background of my New Theory of Art – ANTOA. Started as sociological investigation into the function of Art, a visit to the Kalahari desert, and 24 Arts talks jelled the project. But in human sciences back in the late 1980ies, no real research into the social side of artistic expression took place. I drew up a catalogue of questions and interviewed prominent Arts and Culture vultures in dying days of Apartheid. How did respondents see Art`s function, as firm commitment to building unity and trust, or as solitary glasshouse act, oblivious of social conditions? While concepts like culture, society, civilisation and “tribe” are discussed, the analytical background extends to history of Art in Africa and early inquiries into myth and ritual by B Malinowski and AR Radcliffe-Brown. Malinowski, enchanted by Polynesian creative finesse in limestone pot and canoe carving, fiercely supported the homebound view whereby anthropologists had to see the world thru eyes of the “native”. Malinowski practiced participant observation, a new research technique. Radcliffe-Brown described certain rituals with relation to matrilineal descent rules in a patrimonial society where the child inherits name of the father. While Art serves the function of staving off misfortune and disease. And establishes links to the past as well as to lineage of mother`s brother and sister`s son. The research is focussed on South Africa and draws parallels to Fidji and the Friendly Islands in the Pacific. I end the overview with reference to the shared sentiment of universal character of true Art, that functions like social glue and cements strong links to a mythological past. As well as links among men and material objects, and inside certain social networks. Where the value of tradition is elevated to moral law. And inspires and passes on meaning. Art has indeed gained analytical exposure since and compares favourably to myth and associated ritual activity.